964. Impact of Doxycycline as Malaria Prophylaxis on Risk of Influenza Like Illness Among International Travelers. (26th November 2018) - Lago, Kathryn; Telu, Kalyani; Tribble, David R; Ganesan, Anuradha; Kunz, Anjali; Geist, Charla; Fraser, Jamie; Mitra, Indrani; Yun, Heather
Abstract: Background: International travelers are often at risk for both influenza like illness (ILI) and malaria. Doxycycline is active against many pathogens causing ILI and is routinely used for malaria prophylaxis. We evaluated the incidence of and risk factors for ILI, and whether the choice of malaria prophylaxis was associated with ILI. Methods: TravMil is a prospective observational study enrolling subjects presenting to 6 military travel clinics. We analyzed pre- and post-travel surveys from travelers to regions outside of the continental United States, Western or Northern Europe, Canada, or New Zealand between July 2010 and August 2018. ILI was defined as subjective fever associated with either a sore throat or cough. Characteristics of trip and traveler and the use of malaria prophylaxis were analyzed to determine association with development of ILI. Poisson regression models with robust error variance were used to estimate relative risk of ILI. Results: A total of 3, 227 travelers were enrolled: 62.1% male, median age of 39 (IQR 27, 59), median travel duration 19 days (IQR 12, 49). 32% traveled to Africa, 40% to Asia, and 27% to the Caribbean, Mexico, and Central or South America. Military travel (46%) and vacation (40%) were most common reasons for travel. Twenty percent took doxycycline for malaria prophylaxis, 50% other prophylaxis (89% atovaquone–proguanil), and 30% took none. 8.7% developed ILI. Compared with those on no or other prophylaxis, doxycycline was associated with decreased risk of ILI [RR 0.65 (0.43–0.99), P = 0.046], as was military travel [RR 0.30 (0.21–0.43), P < 0.01]. Increased risk of ILI was associated with female gender [RR 1.57 (1.24–1.98), P < 0.01], travel to Asia [RR 1.37 (1.08–1.75), P = 0.01], cruises [RR 2.21 (1.73–2.83), P < 0.01], and longer duration of travel [RR 1.01 (1.00–1.01, P < 0.01]. Conclusion: The use of doxycycline is associated with a decreased risk of ILI compared with taking no or other malaria prophylaxis. The reasons for this are unclear but may be related to anti-inflammatory effects, activity against bacterial respiratory pathogens, effects on disease transmission in closed populations (e.g., military deploying groups), or other unmeasured factors. With few proven strategies for decreasing ILI risk in travelers, these findings bear further investigation. Disclosures: All authors: No reported disclosures.